Preparation of Activated Carbon from Coffee Grounds as a Supercapacitor Electrode: Pembuatan Karbon Aktif dari Ampas Kopi sebagai Elektroda Superkapasitor - Widayanti; Putra, Pratama Ari (Sunan Kalijaga Journal of Physics, 2025)
The growing demand for sustainable energy storage solutions has spurred interest in supercapacitors, with biomass-derived activated carbon emerging as a promising electrode material. This study investigates the fabrication and performance of activated carbon from spent coffee grounds for application in supercapacitors. Carbonization was carried out at 300°C, 500°C, and 700°C, followed by chemical activation using HCl, KOH, and ZnCl₂. The resulting activated carbons were characterized to determine their physicochemical properties. Optimal activated carbon was obtained at 700°C with KOH activation, yielding 84.75% fixed carbon and conforming to SNI 06-3730-1995 standards. Supercapacitor performance testing revealed that the best results were achieved using electrodes prepared from carbon obtained at 300°C and activated with ZnCl₂, yielding a voltage of 352.9 mV and a capacitance of 465.58 μF after a 1-minute charge. These findings suggest that spent coffee grounds are a viable source of electrode material for efficient, low-voltage supercapacitors.